Three tongkat ali plants (eurycoma longifolia, polyalthia bullata, and stema tuberosa) studied for their aphrodisiac potentials with emphasis on their testosterone boosting capabilities - Yasmin Amirah, Che Yahaya (2021)
Eurycoma longifolia (EL), Pollyathia bullata (PB), and Stema tuberosa (ST) are three species of plants sharing the synonym of "Tongkat Ali" and commonly known as Tongkat Ali Putih, Tongkat Ali Hitam, and Tongkat Ali Merah, respectively. Perhaps they are all known as Tongkat Ali due to their aphrodisiac claims, and parts used are their roots. In this study, three Tongkat Ali plants were tested for safety and efficacy in vivo and in vitro. The roots of the plants were encapsulated and given to fowls. Before being tested on animals, the capsules' content was analysed on a few safety and quality parameters, i.e., pH and moisture tests, heavy metal content, microbial load, and steroid presence. Next, 12 mg of each Tongkat Ali powder included in a capsule was given to fowls for 30 days. The treatment was further extended to 60 days; once found, 30 days was not effective. The outcome showed an increase in testosterone in fowls with the highest value of 9.73 ± 1.20 nmol/L obtained by PB, followed by EL and ST, 7.70 ± 0.59 nmol/L, and 6.25 ± 0.70 nmol/L, respectively. The protein components of these plants were believed to be giving rise to aphrodisiac capabilities. Thus, this study has isolated and characterized the Tongkat Ali species' protein by Bradford assay and SDS PAGE. The highest protein content was EL, i.e., 14.31% ± 3.25, followed by PB and ST, 7.9% ± 2.21 and 6.51% ± 2.03, respectively. The protein of the more popular Tongkat Ali plants, i.e., EL, was removed from the organic constituents with smaller molecular weights using size exclusion chromatography. Next, the protein fraction was further refined by Lectin column chromatography to obtain glycoprotein using a 50% mannose elution buffer. Consequently, the EL, EL glycoprotein, PB, and ST were tested in vitro using TM-3 Leydig cells with a 50 μg/mL concentration. E. longifolia was found to have the highest increase of testosterone secretion of 0.26 ng/mL. This was followed by P. bullata of 0.17 ng/mL, EL glycoprotein of 0.12 ng/mL, and S. tuberosa of 0.07 ng/mL. The outcome showed the aqueos crude extract of EL, EL glycoprotein, PB, and ST confirmed the effects in alleviating the testosterone level in TM-3 Leydig cells. More importantly, the results have proven EL glycoprotein, a pure constituent of EL, can be easily isolated using affinity chromatography to boost testosterone-boosting capabilities. This preliminary study also has provided in vitro and in vivo evidence of testosterone boosting capabilities of the three Tongkat Ali plants, proving that they are all, in fact, aphrodisiac as claimed.